Pre-diagnostic selenium status and hepatobiliary cancer risk in the European Prospective Investigation into Cancer and Nutrition Cohort - Hughes, David J. (Am J Clin Nutr, 2016)
BACKGROUND: Selenium (Se) status is suboptimal in many Europeans, and may be a risk factor for development of various cancers including those of the liver and biliary tract. OBJECTIVE: We wished to examine if Se status in advance of cancer onset is associated with hepatobiliary cancers in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. DESIGN: We assessed pre-diagnostic Se status by measuring serum levels of Se and Selenoprotein P (SePP; the major circulating Se transfer protein) and examined the association with hepatocellular carcinoma (HCC; N=121), gallbladder and biliary tract cancers (GBTC, N=100), and intrahepatic bile duct (IHBC; N=40) cancer risk in a nested case-control design within the EPIC study. Se was measured by total reflection X-ray fluorescence and SePP by a colorimetric sandwich ELISA. Multivariable odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression. RESULTS: HCC and GBTC cases, but not IHBC, had significantly lower circulating Se and SePP levels than their matched controls. Higher circulating Se was associated with a significantly lower HCC risk (OR=0.41, 95%CI: 0.23, 0.72 per 20 μg/L increase) but not with risk of GBTC or IHBC. Similarly, higher SePP concentration was associated with lowered HCC risk only in both the categorical and continuous analyses (HCC: P(trend)=<0.0001; OR=0.37, 95%CI: 0.21, 0.63 per 1.5 mg/L increase). CONCLUSIONS: These findings from a large prospective cohort provide evidence that suboptimal Se status in Europeans may be associated with an appreciably increased risk of HCC development.